Overlap Stevens-Johnson syndrome - Toxic epidermal necrolysis. A case report. - Miteva, L.G.; Tsankov, N.K.; Stoimenov, A.P. (European Journal of Pediatric Dermatology, 1997)
We described a 7-year-old girl who developed severe erythema multiforme-like eruption over the body and extremities after starting Aminophenatonum (Amidopen ®), Paracetamolum (Paracetamol ®), and Phenoxymethylpenicillinum (Ospen ®). There were flaccid blisters on the face with peeling and scalded appearance, bloody crusts on the lips, erosive lesions in the mouth, on the genitalia, and conjunctivitis. The case here reported as well as the review of the other reported cases suggests the close relationship between Stevens-Johnson syndrome and Toxic epidermal necrolysis.